Inverse geochemical modeling of groundwater evolution with emphasis on arsenic in the Mississippi River Valley alluvial aquifer, Arkansas (USA) - Sharif, M.U.; Davis, R.K.; Steele, K.F.; Kim, B.; Kresse, T.M.; Fazio, J.A. (Journal of hydrology (Amsterdam), 2008)
Inverse geochemical modeling (PHREEQC) was used to identify the evolution of groundwater with emphasis on arsenic (As) release under reducing conditions in the shallow (25–30 m) Mississippi River Valley Alluvial aquifer, Arkansas, USA. The modeling was based on flow paths defined by high-precision (±2 cm) water level contour map; X-ray diffraction (XRD), scanning electron microscopic (SEM), and chemical analysis of boring-sediments for minerals; and detailed chemical analysis of groundwater along the flow paths. Potential phases were constrained using general trends in chemical analyses data of groundwater and sediments, and saturation indices data (MINTEQA2) of minerals in groundwater. Modeling results show that calcite, halite, fluorite, Fe oxyhydroxide, organic matter, H 2S (gas) were dissolving with mole transfers of 1.40E − 03, 2.13E − 04, 4.15E − 06, 1.25E + 01, 3.11, and 9.34, respectively along the dominant flow line. Along the same flow line, FeS, siderite, and vivianite were precipitating with mole transfers of 9.34, 3.11, and 2.64E − 07, respectively. Cation exchange reactions of Ca 2+ (4.93E − 04 mol) for Na + (2.51E − 04 mol) on exchange sites occurred along the dominant flow line. Gypsum dissolution reactions were dominant over calcite dissolution in some of the flow lines due to the common ion effect. The concentration of As in groundwater ranged from <0.5 to 77 μg/L. Twenty percent total As was complexed with Fe and Mn oxyhydroxides. The redox environment, chemical data of sediments and groundwater, and the results of inverse geochemical modeling indicate that reductive dissolution of Fe oxyhydroxide is the dominant process of As release in the groundwater. The relative rate of reduction of Fe oxyhydroxide over SO 4 2 - with co-precipitation of As into sulfide is the limiting factor controlling dissolved As in groundwater.